Black Dust: Raymond Queneau and The Encyclopedia of the Inexact Sciences. Issue 2 (July 2019) - McAuliffe, Sam
Abstract : The Encyclopedia of the Inexact Sciences brings together Raymond Queneau's research into an idiosyncratic canon of nineteenth-century works, each written by what he variously refers to as a 'literary lunatic' ( fou littéraire ) or a 'heteroclite.' For Queneau, the work of such an author is discernible less by its subject matter than the discursive position it speaks from: not only does it have no precedent, but so atypical is its standing with respect to the standards of its given field that it cannot be responded to, even provisionally. Hence the guiding principle of The Encyclopedia : 'A " fou littéraire " has neither masters nor disciples.' The body of discourse that takes shape on this basis is drawn upon to more than one end across Queneau's œuvre, but nowhere more ambitiously than in his novel Children of Clay (1938), where it becomes a device for examining the capacities and conditions underwriting the literary object and its institutions. Another of Queneau's discursive experiments in this period, conceived alongside Jean Paulhan, can be understood as a counterpart to The Encyclopedia : as literary editors at Gallimard, they envisaged a collection that would gather together in a single volume the mass of works rejected by the publisher. Bringing this apparently extrinsic, discarded element into circulation would have significant consequences, Queneau argues, not least by exposing the practice of literature to a set of new contexts.